2007
DOI: 10.1089/ten.2007.0096
|View full text |Cite
|
Sign up to set email alerts
|

Review: Gene- and Stem Cell–Based Therapeutics for Bone Regeneration and Repair

Abstract: Many clinical conditions require regeneration or implantation of bone. This is one focus shared by neurosurgery and orthopedics. Current therapeutic options (bone grafting and protein-based therapy) do not provide satisfying solutions to the problem of massive bone defects. In the past few years, gene- and stem cell-based therapy has been extensively studied to achieve a viable alternative to current solutions offered by modern medicine for bone-loss repair. The use of adult stem cells for bone regeneration ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 109 publications
0
114
0
Order By: Relevance
“…A systematic review of gene therapy in bone regeneration can be found in the literature and is not provided here. 40 Bioreactor systems of a variety of designs have also been utilized to enhance the in vitro performance of osteogenic cells before implantation. Bioreactors simulate the 3D dynamic and mechanical in vivo environment and are designed to provide cells seeded deep within a scaffold with all necessary nutrients and biological cues to survive, proliferate, differentiate, and produce ECM.…”
Section: General Principles In Bone Tissue Engineeringmentioning
confidence: 99%
“…A systematic review of gene therapy in bone regeneration can be found in the literature and is not provided here. 40 Bioreactor systems of a variety of designs have also been utilized to enhance the in vitro performance of osteogenic cells before implantation. Bioreactors simulate the 3D dynamic and mechanical in vivo environment and are designed to provide cells seeded deep within a scaffold with all necessary nutrients and biological cues to survive, proliferate, differentiate, and produce ECM.…”
Section: General Principles In Bone Tissue Engineeringmentioning
confidence: 99%
“…During the normal regeneration of a fracture, as seen previously, undifferentiated MSCs, with the assistance of BMPs and regulatory cytokines, proliferate and differentiate into chondrocytes and osteoblasts, which will form bone tissue reconstituting the lesion. Although related to the site where they occur, around 5 to 20% or more of fractures present failure in regeneration and consolidation (Kimelman et al, 2007;Undale, et al, 2009). Experiments on animal models using autologous MSCs and different scaffolds have resulted in bone regeneration (Arinzeh et al, 2003;Bruder et al 1998a, b;Kon et al, 2000;Petite et al, 2000).…”
Section: Applications and Clinical Potentialmentioning
confidence: 99%
“…These strategies involve both the use of viral and non-viral vectors, presenting genes that code different BMPs, as well as genetically modified cells containing these implanted transgenes. The advance of these studies may be essential for the future prospects of clinical use of stem cells for bone regeneration (Kimelman et al, 2007), bringing more efficient solutions in the field of orthopedics.…”
Section: Stem Cells and Gene Therapy: Prospects Of Future Applicationsmentioning
confidence: 99%
“…Recently, genetic engineering technology has been implicated in stem cell-based bone engineering. During this process, geneticallymodified stem cells are used to produce a sustained increase in osteogenic cytokines and growth factors [3], thus subsequently stimulating osteoblast differentiation of the implanted stem cells and the recipient stem cells [3,4]. For example, overexpression of bone morphogenetic protein-2 (BMP-2) in mesenchymal stem cells has been reported to increase new bone formation in bone defects [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of bone morphogenetic protein-2 (BMP-2) in mesenchymal stem cells has been reported to increase new bone formation in bone defects [4]. In addition, genetic engineering of a number of other growth factor genes, such as BMP-4 and -7 [3], and of transcription factors, such as runt-related transcription factor 2 (Runx2) and osterix (Osx) [5][6][7][8], have also been shown to induce osteoblast differentiation of progenitor cells.…”
Section: Introductionmentioning
confidence: 99%